Utilization of Rajiv Aarogyasri Health Scheme by rural policyholders of Chittoor district in Andhra Pradesh - Mannuru, Manjuram (International Journal Of Community Medicine And Public Health, 2019)
Background: Rajiv Aarogyasri has covered 86.53% of the families across the state. Majority of its people are living in rural areas. Hence, our study will explore gaps in accessibility of urban centric health services by rural policyholder’s under the scheme. To find out the current status of Aarogyasri coverage, awareness, utilization and experiences of rural policyholders in Chittoor district of Andhra Pradesh during the year 2014-15. Methods: This is a cross-sectional quantitative study and a total of 200 households were surveyed by using multi-stage random sampling technique to obtain primary data, and for background & discussion secondary data was reviewed. SPSS software was used for data analysis Results: In the past one year, 6.77% of the families have received benefits under the scheme. Amongst the ones who have utilized RAS services, 2/3rd of the families were protected from catastrophic illnesses and the mean average of 91.70% of the total costs was covered by RAS. Another 19.21% of the families were in need of healthcare but did not utilize the services due to lack of RAS card, lack of awareness, non-listed therapies, procedural difficulty, non-availability of caretaker, loss of wage and low quality of services. Conclusions: Overall, 66.66% of the beneficiaries expressed their satisfaction, 16.66% opinionated fair while 16.66% were dissatisfied with the RAS services. Beneficiaries experienced shortage of supportive services in Government hospitals under the scheme. Further, IEC activities, alternatives for excluded conditions, strengthening of public facilities will improve the utilization of RAS and reduce the OOPE.